Managing the Small Aortic Annulus: Which Valve Type Offers Superior Haemodynamic Performance in the Current Era?. (9th April 2021) - Kelly, Ronan; Spence, Mark; Jeganathan, Rueben
Abstract : Objective : The presence of a small aortic annulus (SAA) poses a clinical challenge in patients with aortic stenosis (AS). SAA has been associated with poorer outcomes after aortic valve replacement (AVR), with increased risk of suboptimal valve haemodynamics, prosthesis-patient mismatch (PPM), mortality and cardiovascular events. Recent TAVI trials have demonstrated superior haemodynamic performance compared to conventional SAVR valves. Methods : A retrospective review of the hemodynamic performance as assessed by echocardiography of size 19 Edward's Intuity rapid deployment (RVD) and CE Perimount Magna Ease (SAVR) surgical aortic valves implanted by a single surgeon was performed. The performance of small sized trans-catheter aortic valves (TAVR) (Edwards Sapien 3 Size 20, Medtronic CoreValve size 23) was also analysed. Results : Edwards Intuity size 19 showed statistically superior haemodynamic performance than equivalent sized SAVR (p<0.02; mean 10.6 vs 19.7 mmHg; peak 20 vs 37mmHg). RDV showed equivalent haemodynamic to TAVR valves (mean 10.6 vs 19.8 {Sapien p=0.11} vs 11 {CoreValve p=0.7}; peak 20 vs 36 {Sapien p=0.08} vs 20 {CoreValve p=0.9}). RDV significantly reduces cardiopulmonary bypass (CPB) and aortic X-clamp times compared to conventional SAVR (p=0.001). Conclusions : Among patients with SAA undergoing surgical AVR, Edward's Intuity Size 19 offers superior haemodynamic performance with the added benefit of reduced CPB and X-clamp times.